2011
DOI: 10.5039/agraria.v6i3a1396
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento larval e influência do peso das fêmeas na fecundidade da tilápia do Nilo

Abstract: Desenvolvimento larval e influência do peso das fêmeas na fecundidade da tilápia do Nilo RESUMO O sucesso das etapas subsequentes do cultivo da tilápia do Nilo está diretamente ligado a boas práticas de reprodução da espécie, pois dependem diretamente da qualidade das pós-larvas produzidas. Este trabalho teve por objetivo avaliar o desenvolvimento de tilápia do Nilo em um sistema de incubação artificial e a correlação entre a quantidade de ovos e o percentual de eclosão com o peso total de fêmeas distribuídas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…Actually in most studies which evaluate reproduction characteristics, the body weight is used as a parameter to select animals for experiments due to the standardization and the difficulty of accurate age measurement. Thus, (Almeida et al, 2013) and Moura et al (2011) reported a lower spawning frequency in larger females, coupled to the preference for small animals for better management. Females with more than 300 grams are generally discarded although the opposite was done in current study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually in most studies which evaluate reproduction characteristics, the body weight is used as a parameter to select animals for experiments due to the standardization and the difficulty of accurate age measurement. Thus, (Almeida et al, 2013) and Moura et al (2011) reported a lower spawning frequency in larger females, coupled to the preference for small animals for better management. Females with more than 300 grams are generally discarded although the opposite was done in current study.…”
Section: Resultsmentioning
confidence: 97%
“…However, the best results are obtained when environment and genetics are considered together, trying to offer the best conditions for obtaining maximum performance. Thus, if one decides to keep the females longer on the squad, some factors must be taken into account, such as the need of a larger area for the allocation of females (Moura et al, 2011) since they may easily weigh more than two kilograms. Management may be more difficult and special attention must be given on the renovation of the squad with the emergence of animals with best genetic potential (Bhujel et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Según Little (1989), las hembras de menor tamaño producen más huevos por unidad de peso vivo, mientras que las más grandes producen mayor cantidad de huevos por desove. En la especie O. niloticus se ha determinado que a medida que la talla se incrementa la fecundidad es mayor (Santos et al, 2007;Moura et al, 2011;Mohamed et al, 2013), aunque Desprez et al (2008) no encontraron relación entre la variación del peso corporal y la fecundidad.…”
Section: Introductionunclassified
“…Contudo, as espécies do sexo masculino, presentes no tanque 1, apresentaram um índice melhor que o grupo presente no tanque 2, com alevinos do sexo feminino, com valores de 3,6 e 4,0 respectivamente.Resultados obtidos com espécies do sexo masculino também foram encontradosporAlbino et al (2020), em um estudo similar, com dois grupos de tilápias, as do sexo masculino também apresentaram coloração e maior uniformidade no peso e tamanho. De acordo comMoura et al (2011), isso se dá em razão da espécie apresentar um grande extinto maternal, protegendo seus ovos e alevinos dentro da boca, e assim, dificultando o ganho de massa corporal. Outro agravante, levantado por outro autor, é a alta taxa de reprodução da tilápia, o que gera disputa por espaço, alimento e oxigênio, tornando expressivos os entraves enfrentados pelo piscicultor na produção desta espécie…”
unclassified